Acute effects of low- and high-volume stretching on fitness performance in young basketball players - Andrejic, O. (Serbian Journal of Sports Sciences, 2012)
The purpose of this study was to examine the acute effects of low- and high-volume static and proprioceptive neuromuscular facilitation (PNF) stretching on fitness performance in young basketball players. Twenty-three healthy male basketball players (age, 13.6 ± 0.5 years old; weight, 60 ± 8.4 kg; height, 174.7 ± 7.5 cm; BMI, 19.6 ± 1.6; and basketball training experience 2.5 ± 0.5 years) performed 5 different warm-up protocols in randomly assigned order: (a) no stretching (NS), (b) low-volume static stretching (LVSS), (c) high-volume static stretching (HVSS), (d) low-volume PNF stretching (LVPNF), and (d) high-volume PNF stretching (HVPNF). The low- and high-volume protocols were completed with 2 and 4 sets of stretches respectively. Analysis of the data revealed that vertical jump, long jump and 4x15m standing start running performance declined significantly following LVSS, HVSS, LVPNF, HVPNF as compared to NS (p<0.05). Also, vertical jump, long jump and 4 x 15m standing start running performance were significantly reduced following HVSS as compared to LVSS (p<0.05). Vertical jump and 4 x 15m standing start running performance were significantly reduced following HVPNF as compared to LVPNF (p<0.05). There were no significant differences in flexibility following the 5 warm-up treatments. It appears that pre-performance static and PNF stretches (especially if they are high in volume) may negatively affect motor performance skills in young basketball players.